132k views
4 votes
Solve this system of equations usingthe substitution method.y = 4x + 3y = 7 + 3x=([?], []).

Solve this system of equations usingthe substitution method.y = 4x + 3y = 7 + 3x=([?], []).-example-1
User Mikefolu
by
6.1k points

1 Answer

7 votes

Answer: (4, 19

Given:


\begin{gathered} y=4x+3 \\ y=7+3x \end{gathered}

Substitute the second equation to the first to solve for x:


\begin{gathered} y=4x+3 \\ 7+3x=4x+3 \\ 3x-4x=3-7 \\ -x=-4 \\ x=4 \end{gathered}

Then, we will substitute the value of x to the first equation to solve for y:


\begin{gathered} y=4x+3 \\ y=4(4)+3 \\ y=16+3 \\ y=19 \end{gathered}

The solution would then be (4, 19)

User Wapac
by
6.4k points